Analisys of Inequality Development of the Education Sector in West Sumatra - Jolianis Jolianis; Lovelly Dwinda Dahen; Putri Meliza Sari (Laboratorium Program Studi Pendidikan Sejarah Universitas PGRI Sumatera Barat, 2022)
This study aims to analyze the effect of government spending in the education sector, gender gap, poverty and life expectancy on education inequality. This type of research is associative research. The object of research is the Regency/City in the Province of West Sumatra. The data analysis technique is hypothesis testing, panel data regression analysis with t test. The results of this study found that: 1) Government spending in the education sector has a significant negative effect on educational inequality. 2) The gender gap has a significant positive effect on educational inequality. 3) The level of poverty has a significant positive effect on educational inequality. 4) Life expectancy has a significant positive effect on educational inequality.